Impact of Feed Additives on the Growth of Gourami Fish Seeds (Osphronemus gourami) - Meika Puspita Sari; Khusnul Khotimah; Muhammad Nizar; Elva Dwi Harmilia; Heryadi Heryadi; Ahmad Rahardjo (Universitas Muhammadiyah Palembang, 2023)
The high market demand for gourami has led to an increase in fish farming activities. However, this fish farming activity is constrained by the spawning and breeding process. Gourami fish takes quite a long time in the seed growth phase so it is feared that it can hamper the fulfillment of gourami fish stocks in the market. Several studies have been conducted to shorten the growth time of fish seeds. One of them is in the field of feed. Modification and alternative feed are expected to contribute to science in the cultivation of gourami fish seeds. The purpose of this study was to determine the effect of feeding additives to increase the growth of carp fry (Osphoronemous gouramy). The research was conducted from August to October 2019 using nets in concrete ponds. The research was conducted experimentally using the group randomized design (RAK) method carried out in 4 treatments and 4 groups. The treatments tested were the provision of additional ingredients consisting of P_1 = 15% Probiotic / Kg feed, P_2 = 0.4% Vitamin C / Kg feed, P_3 = 3% Spirulina/kg feed, P_4 = 3.25% Papain enzyme/kg feed. Observation parameters include absolute length growth, absolute weight growth, survival, and feed conversion ratio. The results showed that 3% spirulina/kg and 3.25% papain enzyme/kg had a significant effect on the rate of weight growth and growth.